2012
DOI: 10.1208/s12249-012-9886-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Isomalt for Colon-Specific Delivery and Its Comparison with Lactulose

Abstract: Lactulose is used as a triggering substance in a unique colon-specific delivery technology called CODESTM. Colonic microflora degrades lactulose and forms short-chain fatty acids to activate the CODESTM system. However, lactulose has been reported to cause a Maillard-type reaction with substances containing primary or secondary amino groups that may produce carcinogenic compounds. Thus, the aim of this study was to look into the possibility to substitute lactulose with isomalt for fabrication of CODESTM. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Habitual consumption of isomalt may lead to partial adaptation, which suggests decreased occurrence of gastrointestinal changes. Isomalt could be used as an alternative to lactulose for colonic delivery system utilizing the principles of a unique colon-specific delivery technique called CODES [51]. Since d -glucitol has been associated with greater colonic fermentation compared with isomalt [52], its formation from the latter should be considered.…”
Section: Also Disaccharide Sugar Alcohols May Cause Osmotic Diarrheamentioning
confidence: 99%
“…Habitual consumption of isomalt may lead to partial adaptation, which suggests decreased occurrence of gastrointestinal changes. Isomalt could be used as an alternative to lactulose for colonic delivery system utilizing the principles of a unique colon-specific delivery technique called CODES [51]. Since d -glucitol has been associated with greater colonic fermentation compared with isomalt [52], its formation from the latter should be considered.…”
Section: Also Disaccharide Sugar Alcohols May Cause Osmotic Diarrheamentioning
confidence: 99%
“…Significantly greater level of IFN-g and no difference in the level of IL-4 suggested that Th1/Th2 cell polarization evidently shifted to Th1 cells, and patient's antitumor immunity was significantly enhanced after the administration of lactulose [93]. Many other studies confirmed the positive role of lactulose in the immune defense, immune regulation [94, 95], and activation of cell mediated immune system depressed during liver cirrhosis [92]. …”
Section: Fructans Prebioticsmentioning
confidence: 99%
“…[15] These organic acids lower pH around microenvironment of tablet, dissolving acid soluble polymer completely and thus promoting drug release. [16] CODES TM is a stable formulation which uses a di-dependent approach consisting of pH dependent and microbial activated systems in order to avoid the www.wjpps.com…”
Section: Glycopeptide Nitroimidazole Antidiarrhealmentioning
confidence: 99%
“…However, bioavailability and dissolution studies demonstrated that isomalt and mannitol's performance was equivalent to lactulose in colon targeted delivery system employing the principles of CODES TM . [15,35] Acid soluble polymer: In the CODES™ technology, the purpose of cationic acid-soluble coating is intended to minimize the release of drug in small intestine. It has been studied that in the CODES TM technology, the rate of lactulose availability in the colon for degradation is primarily controlled by the thickness of acid soluble polymer.…”
Section: Eudragit L 100mentioning
confidence: 99%